East Timor : National Development Plan. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses the Poverty Reduction Strategy Paper-National Development Plan for the Democratic Republic of Timor-Leste. The plan has been a participative process, involving constituents in every sector of the economy to identify the problems they face and to suggest solutions to those problems. East Timor's Development Strategy as described in this plan is to design programs and pursue initiatives that systematically address its main development goals. The first set of tasks during this early transition stage is to establish government capabilities, enabling legislation and the institutions required to pursue development priorities.